Carboxymethyl cellulose hydrogel doped with zinc-aspirinate as a multifunctional material: photoprotection, epithelial regeneration, and biocompatibility - Banti, Christina N.; Lezos, Fotakis; Hatzidimitriou, Antonios; Hadjikakou, Sotiris K. (Frontiers in Chemical Biology, 2025)
The synthesis of a new Carboxymethyl Cellulose Hydrogel (CMC) doped with Zinc-Aspirinate (ZnAsp = [Zn(Asp)2(H2O)2]) of formula CMC@ZnAsp is reported. The hydrogel CMC@ZnAsp and its ingredient ZnAsp were characterized by melting point (m.p.) and X-Ray Fluorescence (XRF), Attenuated Total Reflection Fourier-Transform Infrared (ATR-FTIR) and Nuclear Magnetic Resonance (1H-NMR) spectroscopies. The photo-reactivity of CMC@ZnAsp and its constituent ZnAsp under UVB radiation (λmax = 280 nm) was monitoring using 1H-NMR spectroscopy. The in vitro cytotoxicity of both CMC@ZnAsp and ZnAsp was assessed against immortalized human keratinocyte (HaCaT) cells. Their potential role in promoting wound healing—specifically, the growth and migration of new epithelial cells to restore the integrity of the skin—was investigated using a scratch assay on HaCaT cells. Furthermore, the in vitro anti-inflammatory activity of CMC@ZnAsp and ZnAsp was also examined. Their in vivo toxicity was evaluated by Artemia salina assay.